2021
DOI: 10.1007/s00125-021-05617-x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence utilising corneal confocal microscopy for the diagnosis of peripheral neuropathy in diabetes mellitus and prediabetes

Abstract: Aims/hypothesis We aimed to develop an artificial intelligence (AI)-based deep learning algorithm (DLA) applying attribution methods without image segmentation to corneal confocal microscopy images and to accurately classify peripheral neuropathy (or lack of). Methods The AI-based DLA utilised convolutional neural networks with data augmentation to increase the algorithm’s generalisability. The algorithm was trained using a high-end graphics processor for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…Retinal images are usually used to build an automatic diabetic retinopathy diagnosis system (Gardner et al, 1996;Acharya et al, 2009; Ram et al, 2010;Gulshan et al, 2016;Lam et al, 2018;Jiang et al, 2019;Preston et al, 2021). However, whether using traditional machine learning methods (Gardner et al, 1996;Acharya et al, 2009;Ram et al, 2010) or deep supervised learning methods (Gulshan et al, 2016;Lam et al, 2018;Jiang et al, 2019;Preston et al, 2021), they all need a large amount of labeled data during training. In the biomedical image analysis field, labeling work is expensive and the privacy issue is highly sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal images are usually used to build an automatic diabetic retinopathy diagnosis system (Gardner et al, 1996;Acharya et al, 2009; Ram et al, 2010;Gulshan et al, 2016;Lam et al, 2018;Jiang et al, 2019;Preston et al, 2021). However, whether using traditional machine learning methods (Gardner et al, 1996;Acharya et al, 2009;Ram et al, 2010) or deep supervised learning methods (Gulshan et al, 2016;Lam et al, 2018;Jiang et al, 2019;Preston et al, 2021), they all need a large amount of labeled data during training. In the biomedical image analysis field, labeling work is expensive and the privacy issue is highly sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) is a popular technique for computer-aided automatic DR diagnosis to overcome these obstacles and deep learning has achieved progress in biomedical image analysis (Meng et al, 2021b;Preston et al, 2021;Meng et al, 2021a). Yoo and Park (2013) utilized ridge, elastic net, and LASSO to perform validation on 1052 DR patients.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Chen et al [ 81 ] demonstrated comparable efficacy between ACCMetrics and IENFD in diagnosing DPN. Recent advances in the automated analysis of CCM images have utilised DLA [ 88 , 89 , 90 ] and abandoned nerve segmentation in favour of end-to-end classification to allow the DLA to determine features of importance for image classification [ 91 , 92 ].…”
Section: Ccm Image Acquisition and Analysismentioning
confidence: 99%
“…Mou et al [ 125 ] developed a corneal nerve fibre segmentation model based on a dual attention (e.g., spatial and channel attentions) mechanism for the prediction of regions of interest and demonstrated the model’s effectiveness through their automated DLA that demonstrated significant differences in the tortuosity of nerves between patients with diabetes and healthy controls [ 124 ]. Preston et al [ 92 ] developed a DLA using ResNet [ 126 ] as the backbone network to diagnose peripheral neuropathy (in diabetes and prediabetes), achieving a high level of classification accuracy using end-to-end classification ( Figure 2 ). They also demonstrated image attribution-based explainability methods to produce ‘heatmaps’ showing areas in the image which were important to the classification prediction ( Figure 3 ).…”
Section: Ai In Ccmmentioning
confidence: 99%
“…DL-based technology has been applied to retinal vascular segmentation, recognition, and classification of DR lesions, referable DR and diabetic neuropathy detection. Recently, Preston et al developed an AI-based algorithm to classify peripheral neuropathy utilizing CCM without image segmentation prior to classification, which did not require manual or automated annotation and allowed the utilization of a larger database ( 13 ). Most of the above algorithms use the convolutional neural networks (CNN) architecture, which has better performance than other network architectures ( 14 ).…”
Section: Introductionmentioning
confidence: 99%